FILSAFAT DAN CAKUPANNYA DALAM PENDIDIKAN ISLAM - Mustaqim Hajati (Jurnal Tarbiyah Jamiat Kheir, 2023)
The development of education will continue to experience renewal with existing scientific disciplines. This study contains the views and scope that exist in Islamic education through a philosophical perspective. Introductory material in this paper contains a review of ontology, espistemology and axiology to then be able to fully understand Islamic education. Not only definitive and theoretical discussion, but the concept of integration between philosophy and Islamic education is presented to prove that there is relevance between philosophy and renewable education by not forgetting Islamic values. Can see from the scope and scope of existing in Islamic education; the goals, actors, curriculum, methods, evaluation, and educational environment that grow directly in the philosophy of Islamic education. Keywords: Philosophy, Islamic Education, Integration, Scope